IMPACT OF DIVORCE ON CHARACTER EDUCATION OF CHILDREN (CASE STUDY IN PALU SELATAN DISTRICT) - Ismail, Ismail (Risâlah, Jurnal Pendidikan dan Studi Islam, 2021)
The study aims to explore the impact of divorced on children character education especially in morallity. The study was Qualitative approach with the kinds of case study. The results showed that (1) the causes of divorce in South Palu District, namely economic factors, immaturity of the attitude of husband and wife, lack of communication, infidelity, and factors of domestic violence, (2) The positive impacts are: child have reasonable emotional control, show a good orientation towards the future, have high social relations, and show an independent and responsible attitude. While the negative impact children experience stress or mental pressure, children become aggressive and tend to get naughty, and children often have feelings of guilt, children begin to suffer from high anxiety and fear, children can hate one of their parents. and (3) the efforts made by parents based on research findings are reminding children not to expect anything from others (sincerely), sending children to Islamic boarding schools, inviting children to go on recreation, collaborating with neighbors who are close to children, educating children based on life experiences and education with religion honest, tolerant, disciplined, creative and independent character in children.